Does exposure to interparental violence increase women's risk of intimate partner violence? Evidence from Nigeria demographic and health survey - Bola Lukman Solanke (BMC, 2018)
Abstract Background Exposure to interparental violence (EIPV) has been identified as a risk factor for intimate partner violence (IPV). However, studies in Nigeria have rarely and specifically examined exposure to interparental violence as a predictor of IPV. The objective of the study was to examine the relationship between exposure to interparental violence and women's experience of intimate partner violence. Methods The 2013 Nigeria Demographic and Health Survey (NDHS) women recode dataset was analysed. The weighted sample size was 19,925 women aged 15-49 years. The outcome variable was women's experience of at least one type of IPV measured by combining partner physical, sexual and emotional violence experienced by the surveyed women. The main explanatory variable was exposure to interparental violence measured by response to question on whether a woman witnessed her father ever beat her mother. Individual/relationship and community characteristics were selected for statistical control in the study. The multilevel mixed-effect regression was applied in three models using Stata version 12. Model 1 was based solely on interparental violence, while individual/relationship factors were included in Model 2. In Model 3, all research variables were included. Results The study revealed that less than one-tenth of the women witnessed interparental violence, and women exposed to interparental violence compared with non exposed women had higher prevalence of all forms of IPV. In Model 1, women exposed to interparental violence were more than five times as likely as non exposed women to experience IPV (OR = 5.356; CI: 3.371-8.509). In Model 2, women exposed to interparental violence were nearly five times as likely as non exposed women to experience IPV (OR = 4.489; CI: 3.047-6.607). In Model 3, women exposed to interparental violence were four times as likely as non exposed women to experience IPV (OR = 4.018; CI: 2.626-6.147). Conclusion The study provided additional evidence that exposure to interparental violence increase women's risk of IPV in Nigeria. Reducing future prevalence of intimate partner violence may require social and behaviour change communication (SBCC) that not only change perception of children who witnessed interparental violence, but also help them to overcome intergenerational effects of interparental aggression.